Sumber Pakem Tourism Development Strategy through Tourism Area Life Cycle Analysis (Open Society Conference, 2023)
Tourism Area life cycle analysis is one of the steps in determining the right strategic steps in developing tourism objects. Based on the observations that have been made, Sumberpakem tourism has experienced ups and downs despite repeated revitalization. The number of visits is not significant, and even once dropped to a no-tourist phase. The concern is, without proper countermeasures, tourism in SumberPakem will be in a decline phase. The decline phase according to Buttler (2011) is the stage where the destination starts to get saturated, visitors start to get bored so that visits start to show a significant decrease and discontinue. Therefore a research is needed to formulate the right strategy in developing SumberPakem tourism. However, so far no study or research has been conducted. The specific objective of this study is to determine the position of the tourism area life cycle of the SumberPakemtourism area so that strengths, weaknesses, opportunities and threats can be analyzed. The result of this analysis is the formulation of prioritized strategies for sustainable tourism development at SumberPakem. The theory used in this study is the Tourism Area Life Cycle to develop strategy for developing tourist attractions and sustainable tourism. A qualitative descriptive analysis technique was applied to identify data in the form of natural, cultural and man-made potential in SumberPakem. The data were collected by doing a participatory observation technique. The analysis was done by using the Tourism Area Life Cycle theory to identify tourism potential and determine the position of tourism development, and then continued with a SWOT matrix analysis to formulate a tourism development strategy based on its development position.